2017
DOI: 10.1590/2177-6709.22.3.097-108.oar
|View full text |Cite
|
Sign up to set email alerts
|

Miniscrew-assisted rapid palatal expansion for managing arch perimeter in an adult patient

Abstract: Introduction: Etiology of dental crowding may be related to arch constriction in diverse dimensions, and an appropriate manipulation of arch perimeter by intervening in basal bone discrepancies cases, may be a key for crowding relief, especially when incisors movement is limited due to underlying pathology, periodontal issues or restrictions related to soft tissue profile. Objectives: This case report illustrates a 24-year old woman, with maxillary transverse deficiency, upper and lower arches crowding, Class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 28 publications
1
29
0
10
Order By: Relevance
“…[ 18 19 ] Miniscrew-assisted rapid palatal expansion (MARPE) as a nonsurgical technique could be considered an alternative method to correct transverse discrepancy and expand maxilla to increase upper arch length for crowding correction. [ 20 21 ] Thus, the results of this study confirmed that the evaluation of MPS based on CBCT finding is helpful to choose the best treatment planning.…”
Section: Discussionsupporting
confidence: 63%
“…[ 18 19 ] Miniscrew-assisted rapid palatal expansion (MARPE) as a nonsurgical technique could be considered an alternative method to correct transverse discrepancy and expand maxilla to increase upper arch length for crowding correction. [ 20 21 ] Thus, the results of this study confirmed that the evaluation of MPS based on CBCT finding is helpful to choose the best treatment planning.…”
Section: Discussionsupporting
confidence: 63%
“…18,19 MARPE is a less invasive option than SARME, has a skeletal effect, fewer dentoalveolar effects, no surgical risks and reasonably stable results, in addition to being more affordable financially. 20,21 Thus, the objective of this study was to analyze and discuss different treatment approaches for the correction of maxillary deficiencies in patients with advanced skeletal maturation, and describe the treatment of a female patient (14 years and 4 months old) presenting Class II skeletal malocclusion, transverse maxillary hypoplasia and unilateral functional unilateral posterior crossbite -this case was submitted to the Brazilian Board of Orthodontics (BBO).…”
Section: Bbo's Selected Articlementioning
confidence: 99%
“…The activation protocol recommended for MARPE is ¼ of a turn every day, 4 so that the tissues adapt to the forces applied and patient discomfort is minimized, considering the increase in the rigidity of the midpalatal suture with age. 21…”
Section: Bbo's Selected Articlementioning
confidence: 99%
“…Cantarella et al (19) avaliaram quinze pacientes, com idade média de 17,2 anos, após o uso de um expansor esquelético. Observou-se uma abertura da sutura palatina mediana de 4,8mm e 4,3mm na espinha nasal anterior e espinha nasal posterior, respectivamente.…”
Section: Expansores De Ancoragem óSseaunclassified